Crushing impact on liquefaction of various sand soil in Kuantan - Amelia, Victor Dass (2017)
Soil particle breakage is one of the mechanism that govern the behaviour of the soil by altering its grain size distribution, particle shape, void ratio and many other aspects. Granular soil associated with phenomenon such as pile driving experience loading which may cause particle breakage when the loading reaches certain degree. Parallel to soil particle breakage, the physical properties of soil are disturbed which affects the liquefaction resistance of soil. The damage and human casualties caused by liquefaction highlights the importance of analysing soil’s potential to liquefy. As sand soil is the most liquefiable soil among all the classes of soil, it is therefore relevant to study the liquefaction resistance of the soil after it has been crushed, in other word, to study the liquefaction potential of sand soil. The objective of this research is to study the impact of crushing on liquefaction of various sand soil from different locations along the coastal area of East Coast of Peninsular Malaysia. The soil samples were crushed using an automated compactor using fixed numbers of blows to keep constant the level of crushing impact. The soil samples were analysed using a series of test which comprised of sieve analysis test, specific gravity test and relative density test where the physical properties of the soil were studied. These tests were done twice; before and after crushing of sand soil. Few parameters such as Crushing Index were calculated from the changes in particle size distribution. Based on the test results, there is a correlation between the particle breakage due to crushing and its liquefaction potential.